Material Coding for Aircraft Manufacturing Industry - Cai,Hong Xia (2014)
ABSTRACT: Material coding is the basis for enterprises to perform information management. There are various kinds of materials in the aircraft manufacturing industry. In order to improve the efficiency of aircraft material management, this paper studies the aircraft material coding. The aircraft materials are divided into six categories based on some characteristics. The flexible material coding model is proposed consisting of code fields which indicate the material and code field relations in order to define the constraint relations among code fields. There are three kinds of code fields: class code, property code and flow code, while there are three kinds of relations, including the parallel relation, the subordinate relation and the dependency one. For convenient recognition and operation, the alpha-numeric combination code method is used. The material coding system in which the material code could be automatically generated was finally developed. The system has been applied in the aircraft manufacturing enterprise and it has achieved good results.